Accessibility as far as the eye can see: an accessible film festival - Martins, Cláudia (2022)
Currently, we can no longer speak of monolingual societies but rather of a linguistic heterogeneity that cuts across every sector of society. In line with this, numerous international and national laws have been signed; however, few have come into actual effect, as it happens in Portugal. If, on the one hand, we all agree on the need for linguistic mediation for language minorities, e.g. people with sensory impairments, on the other, only scattered measures, initiatives or events can be pinpointed as far as cultural events are concerned, namely in the film industry. Accessible festivals showcase not only films made by people with disabilities, but also festivals that include such modalities as audiodescription, subtitling for the deaf and hard-of-hearing and/or sign language interpreting. Historically speaking, the first film festival to make use of audiodescription is said to be Cannes Festival in 1989 (Benecke, 2011). Others followed suit, but it has been a slow though steady progress to reach the stage where disability has become the focus of some festivals, for instance, in Brazil, San Francisco, USA, or Lyon, France. Therefore, our aim with this paper is two-fold: we seek to review the major national and international film festivals dedicated to disability and/or that provide accessibility so as to understand the array of choices they offer, and report on our accessible cinema festival, a joint organization of the Polytechnic Institute of Bragança and the Avanca Film Club.